Effectiveness of Teaching Programme on Knowledge and Attitude of Mothers Regarding Play of Under Five Children - Bhattarai, Sigma; Bhusal, Chet Kant; Lamichhane, Kavita; Shrestha, Rubina; Chhetri, Pradip (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Play is essential for healthy growth and development of children as it fosters their cognitive, physical, social, and emotional well-being. This study aims to ﬁnd out the effectiveness of teaching program on knowledge and attitude of mothers regarding play of under ﬁve children in a selected municipality of Rupandehi district, Nepal. MATERIAL AND METHODS This was a community based one group pretest and posttest interventional study conducted from December 2020 to May 2021 among 255 mothers of under ﬁve children from randomly selected 3 wards out of the total of 13 wards of Siddharthanagar municipality of Rupandehi district in Nepal. Pretest was followed by educational intervention on play of under ﬁve children and after seven days of educational intervention, posttest was done among same mothers. RESULTS The study found that before intervention, level of knowledge regarding play of under ﬁve children was inadequate among 98.4% of the mothers and attitude was unfavorable among more than three-fourth (76.1%) of the mothers. After the teaching program level of the knowledge was adequate among 100% of the mothers and attitude was favorable among 100.0 % of the mothers. The post-test knowledge mean score was higher than the pretest knowledge mean score with a mean difference of 17.90. The calculated “t” value (-52.92) was highly signiﬁcant with p value < 0.001. Similar to this, there was a mean difference of 21.38 between the mean attitude scores before and after the intervention. The calculated "t" value (-146.80) was highly signiﬁcant with p value < 0.001. CONCLUSION The study concludes that teaching program tends to be effective in enhancing mothers’ knowledge and attitudes towards play of under ﬁve children. Thus, community health nurses should implement such education program on play therapy to mothers of children under ﬁve.